Kesadaran terhadap Isu-isu Kontemporer Haid Berkaitan Al-Quran dalam Mazhab Syafi'i:: Perspektif Tenaga Pengajar al-Quran di Perguruan Tinggi Negara Brunei Darussalam - binti Amir, Nur Awadah Aqilah; bin Mahmud, Hafini (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
Menstruation is the natural flow of blood from a woman's uterus after reaching puberty and at specific times. According to the Shafi'i School of thought, one of the things forbidden for menstruating women is reading, touching, and carrying the Quran. However, some female students at universities in Brunei Darussalam still lack knowledge and understanding of the rules relating to menstruation and the Quran. Therefore, this study aims to assess awareness of contemporary issues regarding menstruation as they arise in relation to the Quran according to the Shafi'i School of thought among female university students in Brunei Darussalam. This study employed a qualitative approach through analysis of data obtained from interviews and literature review. The results indicate that, despite numerous legal explanations in Islamic scriptures and other literatures, confusion and lack of understanding persist among female students regarding these matters. In fact, some of them have even unknowingly become accustomed to following these prohibitions. As a recommendation, this study emphasizes the importance of strengthening ongoing religious education and more in-depth Islamic jurisprudence (fiqh) teaching to further enhance the understanding of female students and the general public regarding menstruation issues related to the Quran according to the Shafi'i of thought.